1993
DOI: 10.1002/1097-0142(19930915)72:6<1866::aid-cncr2820720613>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

The association between transfusion and cancer-free survival after curative resection for hepatocellular carcinoma

Abstract: Background. In cases of surgery for hepatocellular carcinoma (HCC), postoperative intrahepatic recurrence is the main obstacle to long‐term survival of patients. The association between perioperative transfusion and recurrence‐free survival was studied in 126 patients with HCC who underwent hepatic resection between 1985 and 1990 and in whom complete follow‐up information was available until 1992. Methods. Patients who received neither whole blood nor packed erythrocytes during hospitalization formed the no tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 22 publications
4
44
0
1
Order By: Relevance
“…The role of perioperative blood transfusion on intrahepatic recurrence of HCC was first suggested by Yamamoto et al [28], whereas Matsumata et al [29] reported that the association between blood transfusion and recurrence-free survival was recognized, but only in patients without intrahepatic metastasis. Furthermore, Makino et al found that the association between perioperative blood transfusion and the cancer-free survival could only be detected in HCC patients with portal vein invasion [30].…”
Section: Discussionmentioning
confidence: 99%
“…The role of perioperative blood transfusion on intrahepatic recurrence of HCC was first suggested by Yamamoto et al [28], whereas Matsumata et al [29] reported that the association between blood transfusion and recurrence-free survival was recognized, but only in patients without intrahepatic metastasis. Furthermore, Makino et al found that the association between perioperative blood transfusion and the cancer-free survival could only be detected in HCC patients with portal vein invasion [30].…”
Section: Discussionmentioning
confidence: 99%
“…Asahara et al [3] also reported that transfusion was a significant prognostic indicator of recurrence in stages I-II patients, but not in stages III-IV patients. On the other hand, Matsumata et al [36] and Kwon et al [37] reported that there was no association between erythrocyte transfusions and recurrence-free survival. Our data are not sufficient to prove that minimizing transfusions leads to a survival benefit, because this study did not include a second control group with standard postoperative treatment without restriction of blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Allogenic blood transfusion has been reported to be related to decreased survival in some types of neoplasms. [1][2][3][4][5][6][7][8] However, the significance of the effect of allogenic blood transfusion on the prognosis of patients with malignant tumors has not necessarily been determined because there also have been some reports that emphasized the finding that no significant correlation was observed between allogenic blood transfusion and prognosis in patients with malignant tumors. 9 -12 Decreased survival in patients with esophageal carcinoma who have received an allogenic blood transfusion have been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…R eception of an allogenic blood transfusion has been reported to be correlated with decreased survival in patients with carcinoma of the colon and rectum, 1-3 stomach, 4 breast, 5 liver, 6,7 and lung. 8 The correlation between blood transfusion and decreased survival in patients with malignant tumors has been discussed from the viewpoint of the nonspecific immunosuppression derived from a blood transfusion.…”
mentioning
confidence: 99%